Psychometric Properties of the Inventory of School Difficulties in Adolescents (Isda) Within the Chilean Population - Vera-Villarroel, P (UNIV ALMERIA, FAC HUMANIDADES & CIENCIAS EDUC, DEPT PSICOL EVOLUTIVA & EDUC, 2018)
Recent studies have indicated that health-risk behaviors and behavioral problems are appearing increasingly at a younger age within the Latin-American population. The Inventory of School Difficulties in Adolescents (ISDA. Martinez-Gonzalez & Vera-Villarroel, 2013) is a new screening scale of 13 items that assesses behavioral problems and common risky behaviors highly relevant within educational settings, especially related to school failure. The aim of this study is to examine the psychometric properties and factor structure of the ISDA. The ISDA, a social-demographic questionnaire and a measure of anxiety and depression symptoms were applied to a sample of 719 Chilean adolescents. The results indicate that the ISDA contains a bi-factor structure: behavioral problems and risky behaviors for health. Estimations of internal consistency and test-retest reliability, as well as evidences of convergent-discriminant validity were adequate. Therefore, the ISDA is an adequate screening tool for assessing risky behaviors and behavioral problems for Chilean adolescents within school settings.